PENGARUH FASILITAS KERJA DAN KEPEMIMPINAN TERHADAP KINERJA PEGAWAI DENGAN MOTIVASI KERJA SEBAGAI PEMODERASI DI BADAN PENGELOLAAN KEUANGAN DAN ASET DAERAH KOTA YOGYAKARTA - Adi Nugroho, Priyo; Widiastuti, Nur (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2024)
The study aimed to determine and analyze the effect of work facilities and leadership on employee performance with work motivation as a moderating variable at the Yogyakarta City Government Regional Financial and Asset Management Agency. The study used 134 data obtained through a saturated sampling technique. Data analysis utilized multiple linear regression tests and Moderated Regression Analysis. The findings show that work facilities and leadership influence employee performance at the Yogyakarta City Government Regional Financial and Asset Management Agency. Work motivation cannot moderate the effect of work facilities and administration on employee performance of the Yogyakarta City Government Regional Financial and Asset Management Agency. The Yogyakarta City Regional Financial and Asset Management Agency is expected to maintain adequate facilities and update them with more up-to-date work facilities to support employees. In addition, the leadership of the Yogyakarta City Regional Financial and Asset Management Agency is expected to maintain and update its leadership style following the times and see the conditions of the work environment so that it can continue to provide the best leadership to improve the performance of its employees.